2005
DOI: 10.1128/jcm.43.10.5384-5387.2005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Progression of Methicillin-Resistant Staphylococcus aureus Vertebral Osteomyelitis Associated with Reduced Susceptibility to Daptomycin

Abstract: Daptomycin, a novel cyclic lipopeptide antibiotic, exhibits rapid bactericidal activity in vitro against most clinically relevant gram-positive organisms, including drug-resistant pathogens. Herein we describe a patient in whom methicillin-resistant Staphylococcus aureus with reduced susceptibility to daptomycin was responsible for bacteremia and progressive vertebral osteomyelitis during daptomycin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 9 publications
2
32
0
1
Order By: Relevance
“…Mutations in mprF and yycG are further implicated by their identification in nonsusceptible isolates that have emerged in the clinic after weeks of daptomycin therapy (13,41). These results suggest that selective pressures found in laboratory serial-passage experiments parallel the selective pressures encountered in clinical settings, particularly in difficult infections where organisms might not be exposed to adequate levels of antibiotic (e.g., undrained abscess, dead bone).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Mutations in mprF and yycG are further implicated by their identification in nonsusceptible isolates that have emerged in the clinic after weeks of daptomycin therapy (13,41). These results suggest that selective pressures found in laboratory serial-passage experiments parallel the selective pressures encountered in clinical settings, particularly in difficult infections where organisms might not be exposed to adequate levels of antibiotic (e.g., undrained abscess, dead bone).…”
Section: Discussionmentioning
confidence: 58%
“…The MIC for 90% of the S. aureus strains tested is 0.5 g/ml, and surveillance studies have not reported any strains for which the MIC is Ն4 g/ml (5, 34). Rare treatment-emergent S. aureus strains for which the MICs are 2 to 4 g/ml have been reported (13,41). This study demonstrates that an accumulation of mutations over time correlates with incremental increases in the daptomycin MIC.…”
mentioning
confidence: 59%
“…Several studies have been performed with daptomycin-resistant strains derived in vitro (16,19,33,47,50), yet the mech- (23) described a reduced susceptibility to daptomycin-induced depolarization, permeabilization, and autolysis, as well as a significantly lowered surface binding of daptomycin and increased cross-resistance to the cationic antimicrobial host defensins hNP-1 and tPMP-1. Although the membrane has been regarded as the main target for daptomycin, our group observed a strong correlation between the presence of a thickened cell wall and daptomycin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Daptomycin exhibits rapid bactericidal activity in vitro and causes membrane depolarization, which leads to potassium release and cell death (48). Despite the effectiveness of daptomycin that has been shown during clinical trials, strains nonsusceptible both in vitro and in vivo have already been isolated (19,25,33,47,50).…”
mentioning
confidence: 99%
“…Este hecho parece no afectar a su actividad bactericida 12,13 . La tasa de mutantes resistentes espontáneas in vitro a la daptomicina es baja 14 , pero se han encontrado algunos aislados clí-nicos de S. aureus y Enterococcus con sensibilidad disminuida a este compuesto [15][16][17][18] . Los ensayos clínicos realizados hasta la fecha con daptomicina demuestran su equivalencia frente a tratamientos estándares en infecciones de piel y de tejidos blandos, bacteriemia y endocarditis bacteriana [19][20][21] .…”
Section: Introductionunclassified